2020
DOI: 10.3390/polym12061380
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a New In-Situ Measurement System for the Study of Touch-Feel Relevant Surface Properties

Abstract: The touch-feel sensation of product surfaces arouses growing interest in various industry branches. To entangle the underlying physical and material parameters responsible for a specific touch-feel sensation, a new measurement system has been developed. This system aims to record the prime physical interaction parameters at a time, which is considered a necessary prerequisite for a successful physical description of the haptic sensation. The measurement setup enables one to measure the dynamic coefficient of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…It was observed that the exponential component of the normal force β, which was obtained from (4), was not constant and varied randomly, despite the same finger rubbing the same artificial skin surface under identical lubrication conditions. Previous studies have shown that β depends on various factors such as the material, lubrication conditions, and surface roughness [1,[8][9][10][11][12]15]. However, the dependence of the cof on the normal force is random, despite maintaining identical tribological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that the exponential component of the normal force β, which was obtained from (4), was not constant and varied randomly, despite the same finger rubbing the same artificial skin surface under identical lubrication conditions. Previous studies have shown that β depends on various factors such as the material, lubrication conditions, and surface roughness [1,[8][9][10][11][12]15]. However, the dependence of the cof on the normal force is random, despite maintaining identical tribological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1. Various studies investigating the frictional forces acting on human skin focus on their dependence on the normal force, i.e., the exponent β in (4) [1,[8][9][10][11][12][13][14]. Because adhesion friction is a dominant force acting on dry human skin [4,[15][16][17], the real contact area responsible for the adhesion friction and its dependence on the normal force are two important factors as well [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize, the perception of a surface and its haptic properties are significantly influenced by roughness and microstructure, respectively, whereby non-negligible parameters include friction, contact area, temperature, and humidity between the human finger and the examined surface [ 24 ]. In particular, for a scientific investigation on haptic influences, the production of samples with a defined surface structure is indispensable.…”
Section: Introductionmentioning
confidence: 99%